2010
DOI: 10.1128/jvi.02638-09
|View full text |Cite
|
Sign up to set email alerts
|

Env-Expressing Autologous T Lymphocytes Induce Neutralizing Antibody and Afford Marked Protection against Feline Immunodeficiency Virus

Abstract: The envelope (Env) glycoproteins of HIV and other lentiviruses possess neutralization and other protective epitopes, yet all attempts to induce protective immunity using Env as the only immunogen have either failed or afforded minimal levels of protection. In a novel prime-boost approach, specific-pathogen-free cats were primed with a plasmid expressing Env of feline immunodeficiency virus (FIV) and feline granulocyte-macrophage colony-stimulating factor and then boosted with their own T lymphocytes transduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…A recent study showed that immunization with FIV Pet Env-expressing autologous T cells conferred protection against a homologous challenge and correlated with immunization-induced NAbs [41]. In line with this, both active and passive immunizations in our studies conferred protection against homologous tier-1 FIV Pet .…”
Section: Discussionsupporting
confidence: 87%
“…A recent study showed that immunization with FIV Pet Env-expressing autologous T cells conferred protection against a homologous challenge and correlated with immunization-induced NAbs [41]. In line with this, both active and passive immunizations in our studies conferred protection against homologous tier-1 FIV Pet .…”
Section: Discussionsupporting
confidence: 87%
“…Plasmids p239SpSp5= and p239SpE3=, encoding the SIVmac239 molecular clone 5= and 3= ends, respectively (30,49), were obtained through the AIDS Research and Reference Reagent Program (ARRP), Division of AIDS, NIAID, NIH. The plasmid encoding the envelope of the in vivo-readapted FIV strain Petaluma (FIV-Petaluma) (pEE14-Env) was described elsewhere previously (47).…”
Section: Methodsmentioning
confidence: 99%
“…Although the result from Study 1 is not statistically significant, T cells appeared to be involved in conferring A-T protection, but the number of B-cell recipients was too small to determine whether B cells alone can confer A-T protection. In regards to the potential of B cells to afford protection to recipients of A-T, studies by others have shown that the commercial dual-subtype FIV vaccine [31] as well as priming T cells with FIV Pet Env pDNA [32] induced high NAbs to FIV Pet . However, in current studies, all recipients of A-T from vaccinated cats, except for the unprotected recipients, had no NAbs to FIV Pet or FIV FC1 (data not shown) and no FIV Abs (Tables 2 and 3, immunoblot).…”
Section: Discussionmentioning
confidence: 99%